2013
DOI: 10.1176/appi.focus.11.3.396
|View full text |Cite
|
Sign up to set email alerts
|

Review: Managing Posttraumatic Stress Disorder in Combat Veterans With Comorbid Traumatic Brain Injury

Abstract: Military deployments to Afghanistan and Iraq have been associated with elevated prevalence of both posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI) among combat veterans. The diagnosis and management of PTSD when a comorbid TBI may also exist presents a challenge to interdisciplinary care teams at Department of Veterans Affairs (VA) and civilian medical facilities, particularly when the patient reports a history of blast exposure. Treatment recommendations from VA and Department of Defense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 159 publications
0
9
0
Order By: Relevance
“…Yin et al ( 2011 ) also showed that patients with PTSD had reduced spontaneous activity in the cerebellum. While concurrent diagnoses of mTBI and PTSD are difficult due to common symptoms and problems with self-report assessments (Capehart and Bass, 2012 ), there may still be relatively high rates of PTSD within the population of patients who have experienced mTBI (Hoge et al, 2008 ; Rosenfeld and Ford, 2010 ; Graner et al, 2013 ). In our study, reduced spontaneous cerebellar activity in acute mTBI patients may subserve cognitive and emotional impairment disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al ( 2011 ) also showed that patients with PTSD had reduced spontaneous activity in the cerebellum. While concurrent diagnoses of mTBI and PTSD are difficult due to common symptoms and problems with self-report assessments (Capehart and Bass, 2012 ), there may still be relatively high rates of PTSD within the population of patients who have experienced mTBI (Hoge et al, 2008 ; Rosenfeld and Ford, 2010 ; Graner et al, 2013 ). In our study, reduced spontaneous cerebellar activity in acute mTBI patients may subserve cognitive and emotional impairment disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Blast-related mTBI appears to increase the risk of post-traumatic stress disorder (PTSD) with a substantial overlap between mTBI and PTSD issues ( 3 , 4 ). Military deployments to Afghanistan and Iraq have been associated with an elevated prevalence of both PTSD and mTBI among combat veterans ( 5 7 ) The diagnosis and management of PTSD when a comorbid mTBI may also exist presents a challenge to interdisciplinary care teams at the Department of Veterans Affairs (VA) and civilian medical facilities, particularly when the patient reports a history of blast exposure ( 8 ). From a treatment perspective, trauma-focused cognitive behavioral therapy (TF-CBT) is the therapy that is associated with superior improvement in PTSD symptoms and psychosocial outcome in mTBI survivors ( 9 ) with a slight advantage compared to all other treatments ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…34 Capehart and Bass reviewed the Department of Defense/ Veteran's Affairs Clinical Practice Guideline (VA/DoD CPG) for the Management of PTSD in the context of treatment of comorbid TBI. 62 First-line recommendations were sertraline and citalopram. Second-line choices included fluoxetine, mirtazapine, or nefazodone.…”
Section: Behavioral Interventionsmentioning
confidence: 99%